The semiotic and modern hermeneutic review of the online Covid-19 public service advertisement texts - Astawa, I Gede; Upadana, I Bagus Gede; Srikandi Putri, A.A. Sagung Ayu (Englisia: Journal of Language, Education, and Humanities, 2023)
The Indonesian government works closely with other agencies to intensely campaign for the movement against the virus corona in various ways, one of which is through Public Service Advertisements (PSAs). PSAs have verbal and non-verbal elements that contain meanings, both explicit and implicit meanings. This article aims to analyze three samples of PSAs concerning Covid-19 retrieved from three online website media, namely (1) the website of the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia; (2) Republika online; and (3) Kompas.com. This research was conducted using qualitative descriptive methods referring to the semiotic theory developed by Roland Barthes and Charles Sanders Peirce, and the modern hermeneutics theory developed by Paul Ricoeur. The analysis of the PSAs in this study was focused on verbal texts, while non-verbal texts were not analyzed deeply. From the three PSAs analyzed, the study found that the explicit meanings lying in the PSAs were to fight the coronavirus by complying with health protocols. Meanwhile, implicitly, the PSAs imply that the Indonesian people are under threat of death, the coronavirus is not a lie, nor is it a conspiracy.